Cuprizone‐induced graded oligodendrocyte vulnerability is regulated by the transcription factor DNA damage‐inducible transcript 3. Issue 2 (3rd December 2018) - Fischbach, Felix; Nedelcu, Julia; Leopold, Patrizia; Zhan, Jiangshan; Clarner, Tim; Nellessen, Lara; Beißel, Christian; van Heuvel, Yasemin; Goswami, Anand; Weis, Joachim; Denecke, Bernd; Schmitz, Christoph; et al.
Abstract: Oligodendrocytes are integral to efficient neuronal signaling. Loss of myelinating oligodendrocytes is a central feature of many neurological diseases, including multiple sclerosis (MS). The results of neuropathological studies suggest that oligodendrocytes react with differing sensitivity to toxic insults, with some cells dying early during lesion development and some cells being resistant for weeks. This proposed graded vulnerability has never been demonstrated but provides an attractive window for therapeutic interventions. Furthermore, the biochemical pathways associated with graded oligodendrocyte vulnerability have not been well explored. We used immunohistochemistry and serial block‐face scanning electron microscopy (3D‐SEM) to show that cuprizone‐induced metabolic stress results in an "out of phase" degeneration of oligodendrocytes. Although expression induction of stress response transcription factors in oligodendrocytes occurs within days, subsequent oligodendrocyte apoptosis continues for weeks. In line with the idea of an out of phase degeneration of oligodendrocytes, detailed ultrastructural reconstructions of the axon–myelin unit demonstrate demyelination of single internodes. In parallel, genome wide array analyses revealed an active unfolded protein response early after initiation of the cuprizone intoxication. In addition to the cytoprotective pathways, the pro‐apoptotic transcription factor DNA damage‐inducible transcript 3 (DDIT3) was induced early in oligodendrocytes. In advanced lesions, DDIT3 was as well expressed by activated astrocytes. Toxin‐induced oligodendrocyte apoptosis, demyelination, microgliosis, astrocytosis, and acute axonal damage were less intense in the Ddit3 ‐null mutants. This study identifies DDIT3 as an important regulator of graded oligodendrocyte vulnerability in a MS animal model. Interference with this stress cascade might offer a promising therapeutic approach for demyelinating disorders. Abstract : Metabolic oligodendrocyte injury is a graded process. Graded metabolic oligodendrocyte injury is regulated by ER‐stress. Ddit3 regulates oligodendrocyte apoptosis.